The local antimagic on disjoint union of some family graphs - Marsidi Marsidi (Department of Mathematics, UIN Sunan Ampel Surabaya, 2019)
A graph  in this paper is nontrivial, finite, connected, simple, and undirected. Graph  consists of a vertex set and edge set. Let u,v be two elements in vertex set, and q is the cardinality of edge set in G, a bijective function from the edge set to the first q natural number is called a vertex local antimagic edge labelling if for any two adjacent vertices and , the weight of  is not equal with the weight of , where the weight of  (denoted by ) is the sum of labels of edges that are incident to . Furthermore, any vertex local antimagic edge labelling induces a proper vertex colouring on where  is the colour on the vertex . The vertex local antimagic chromatic number  is the minimum number of colours taken over all colourings induced by vertex local antimagic edge labelling of . In this paper, we discuss about the vertex local antimagic chromatic number on disjoint union of some family graphs, namely path, cycle, star, and friendship, and also determine the lower bound of vertex local antimagic chromatic number of disjoint union graphs. The chromatic numbers of disjoint union graph in this paper attend the lower bound.